Lichens of Desniansko-Starogutsky National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
146 species of the lichens on Desniansko-Starogutski National Nature Park (Sumy region, Seredyno-Budsky district) were given. Among them Сalicium glaucellum, Chaenotheca laevigata, C. xyloxena, Lecanora compallens, Protoparmelia oleagina, Rinodina efflorescens, Xylographa vitiligo are new species for plain part of Ukraine. 76 species are new for the national park. The Starogutska part of the park is represented by 115 species of the lichens in contrast of Desnjanska part has 80 species only. 126 species of the lichens were corticolous. Low number of the woodland key habitat-indicator lichens related with intensive forestry on this territory to the creation of the national park. Evernia mesomorpha and Punctelia jeckeri are recommended to the Red Data List of the Sumy region. The annotated list of the species is provided.
Keywords: forest, Desna, Ulutsa, Stara Guta, Sumy region, Ukraine.